Investigation on Mechanical properties of Partial replacement of Saw-Dust to Fine-Aggregate in Coconut-Shell Concrete - S, Anandh; K, Gunasekaran (International Journal of Engineering and Technology, 2018)
Concrete is the major composite material used in construction industry, it is strong in Compression and weak in tension and also has high self-weight. The light weight concrete was a alternative to conventional concrete due its low weight it decreases the self weight. Comparatively by using the light weight materials that occur either naturally or industrial waste, these material helps in reducing the cost and to improve the performance. Presently in India, more than 960 million tones of solid waste were being generated annually as by-products during industrial, agricultural mining and other processes. This paper deals with coconut shell concrete, which is one of the solid waste in the environment, and the use of this coconut shell as a replacement to coarse aggregate will reduce the weight of concrete by 25%. The other waste that was disposed mostly was sawdust. It was a byproduct of cutting or drilling of wood with saw or other tool. It is composed of fine particles of wood. It is having many advantages over traditional concrete like low bulk density, better heat preservation and heat insulation property. As said earlier to make concrete strong in tension coconut fiber is added, which is a waste material that left to disposal and as it is strong and stiff will hold the concrete material and also controls the crack. This study investigates on the use of sawdust as partial replacement for fine aggregates in concrete production. Sawdust was used to replace fine aggregates in Conventional and as well as in Coconut Shell concrete from 0%, 5%, 10% and 20%. M25 grade of concrete was selected and testing is evaluated at age of 3, 7 and 28 days. From the results, increase in percentage of saw-dust in concrete cubes led to corresponding reduction in compressive strength values, and the optimum saw-dust content was obtained at 5% in conventional as well as in coconut shell concrete , coconut fiber was added at the optimum value of sawdust on conventional and coconut shell concrete at 1%,2%,3%,4% and 5%. The better strength was obtained at 2% addition of fiber in coconut shell concrete and at 3% addition in conventional concrete.Â